Transaksi – transaksi yang dilarang oleh Islam - Fadilla, Zenita Arsya; Anggraini, Mentari Cahya Dwi (Maliki Interdisciplinary Journal, 2024)
Islam has regulated trade in the market so that competition between traders in the market is carried out in a fair and honest manner. All forms of transactions that cause injustice and that can results in a tendency to increase the price of goods unjustly are strictly prohibited in Islam. This paper will discuss transaction that are prohibited by Islam. In worship, the legal rule that applies is that all things are prohibited, except those that are provisions based on the Al-Qur’an and Al-Hadith. Meanwhile, in matters of muamalah, everything is permitted unless there is an argument that prohibits it. This means that when a new transaction appears and is not previously known in Islamic law, then the transaction is considered acceptable, unless there are implications from the Koran and Hadith that prohibit it, either explicitly or implicitly. Thus, in the field of muamalah, all transactions are permissible except those that are prohibited.